A comparative study of ferrous and persulfate catalysts for the H2O2/UV oxidation of batik wastewater - Regita Syahra Ramadhan; Arseto Yekti Bagastyo (Center for Science and Technology, IAIN Surakarta, 2024)
The increasing number of batik industries in Indonesia may lead to water pollution due to wastewater containing high levels of organic pollutants. This study evaluated advanced oxidation processes (AOPs) utilising H2O2/UV to decolourise and remove organic contaminants (measured as chemical oxygen demand, COD) from batik wastewater. The study aims to compare the effectiveness of adding ferrous and persulfate as catalysts as catalyst in the H2O2/UV process, specifically evaluating the H2O2/Fe2+/UV and H2O2/S2O82-/UV processes. The results indicated that all treatment methods effectively decolourised and degraded COD in the batik wastewater. COD and colour removal achieved up to 96.51% and 78.70% for H2O2/UV, 97.20% and 83.53% for H2O2/Fe2+/UV, and 97.20% and 83.53% for H2O2/ S2O82-/UV, processes, respectively. Additionally, the use of persulfate as a catalyst accelerated the oxidation processes, reaching completion in 45 minutes compared to 60 minutes with the other catalyst.